Prolonged blockade of NMDA receptors and positive modulation of α5 GABAA receptors: no changes in depressive- like behavior, while the former slightly increased emotional reactivity in unstressed rats - Djorovic, Djordje; Ivanovic, Jana; Jezdic, Kristina; Sharmin, Dishary; Arandjelovic, Jovana; Cook, James; Savic, Miroslav (Medical Research, 2025)
Introduction: Depression is a multifaceted disorder with a limited therapeutic repertoire. A significant breakthrough in depression research has been the discovery of fast-acting antidepressants that target the glutamate/GABA system, namely ketamine and neurosteroids. Positive modulation of GABAA receptors containing the α5 sub-unit (α5GABAARs) represents a promising new approach for targeted therapy of depression. The aim of this study was to investigate the effects of repeated administration of ketamine, an NMDA antagonist, and GL-II-73, a positive allosteric modulator at α5GABAARs, on behavioral despair, anxiety, and locomotor activity.Material and Methods: The experiments were performed on adult male Sprague-Dawley rats. Animals were treated for 7 days with either 6 mg/kg or 10 mg/kg ketamine in an intermittent dosing regimen, 10 mg/kg GL-II-73, or solvent. Following treatment, we performed a battery of behavioral tests consisting of forced swim test (FST), spontaneous locomotor activity (SLA), and novelty suppressed feeding test (NSFT).Results: No change was detected in any of the treatment groups regarding performance in the FST and NSFT. In SLA, all forms of treatment caused a decrease in the percentage of central time at both 10 and 30 minutes. Central distance was reduced at 10 and 30 minutes only after the 10 mg/kg dose of ketamine.Conclusion: Ketamine at the higher dose (10 mg/kg) elicited behavioral changes consistent with a slight increase in emotional reactivity, while minor changes of the same quality in the lower-dose ketamine and GL-II-73 groups hardly reflect any anxiety-inducing influence.
Keywords: Depression; Anxiety; Ketamine; α5 GABAA receptor modulation